Naik dango pada masyarakat Daya Kendayan - Aten, Herculanus (s.n., 1989)
Thanksgiving festival after harvesting time by Dayak ethnic group of Kabupaten Pontianak and Kabupaten Sambas, Kalimantan Barat Province.